Heavy metal accumulation (Cu and Pb) fromn artificially contaminated sediment by a Marine - Naresh Kumar s/o Appadurai (2014)
In this experiment, the bivalve clams Geloina sp. were subjected to the standard 28 day bioaccumulation and 14 day depuration study in artificially contaminated sediment.